The Bahamas. Significant achievements 2020 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2021)
The main activities carried out by the Institute in the Bahamas during 2020 are identified, with respect to the needs and interests of the country, identifying support in agro-tourism, environment, food security and climate change. Likewise, among the achievements carried out, the progress of the different projects implemented, the extension activities in the dissemination of information with publications, forums, training and research are recognized.